Synopsis: Agricultural growth and poverty in Mozambique: Technical analysis in support of the Comprehensive Africa Agriculture Development Program (CAADP) - Pauw, Karl; Thurlow, James; Uaiene, Rafael; Mazunda, John (International Food Policy Research Institute, 2015)
In any economy there are important economic linkages and trade-offs to be considered when designing policies or assessing their impacts. One of the policy analysis tools that can help policymakers understand those linkages and trade-offs is an economywide computable general equilibrium (CGE) model. This policy note presents the results of a study that calibrates a CGE model to Mozambique’s newest social accounting matrix to consider economywide growth, poverty, and nutrition impacts under alternative agricultural growth scenarios. Scenarios are compared over the period 2009 to 2019, which coincides with the implementation period of the Strategic Plan for Agricultural Development (Plano Estratégico de Desenvolvimento Agrário [PEDSA]), Mozambique’s embodiment of the Comprehensive Africa Agriculture Development Program (CAADP).